Exploring farmers’ communication pattern and satisfaction regarding the adoption of Agromet advisory services in semi-arid regions of southern India - Rohit, Jagriti; Bal, S. K.; Anshida Beevi, C. N.; Nagasree, K.; Ravi Shankar, K.; Nirmala, G.; Pushpanjali,; Samuel, Josily; Veni, V. Girija; Nagarjuna Kumar, R.; Pankaj, Prabhat Kumar; Prabhakar, Mathyam; et al. (Frontiers in Sustainable Food Systems, 2024)
Agriculture is significantly impacted by the variability in weather patterns, imposing substantial constraints on farmers’ ability to make informed tactical and strategic decisions regarding their crops. Seasonal climate projections have shown potential for informing agricultural decisions, but the actual adoption of climate information by farmers has been relatively slow and limited. The present study was conducted with the objective of investigating the characteristics of adopters, the communication network, and the level of farmer’s satisfaction concerning the adoption and continued use of Agromet Advisories Services (AAS). Two semi-arid districts, namely Kurnool and Anantapur in Andhra Pradesh, were purposively selected, wherein 280 farmers constituted the sampling frame. In this study, social network analysis (SNA) was conducted to examine the peer-to-peer communication patterns, while importance-performance analysis (IPA) was employed to evaluate farmer’s satisfaction, contributing to the continued adoption of AAS. The findings revealed that with regard to personality and communication characteristics, farmers were in the low category for their ability to cope with uncertainties and risk and even for their information-seeking behavior. Furthermore, the results showed farmers to be highly satisfied with the overall adoption of AAS. However, the IPA matrix revealed that among the nine attributes, the credibility of the forecasts needed refinement to promote sustained adoption. Excessive emphasis was placed on attributes such as the frequency of forecasts, which could be channeled into other initiatives. Peer-to-peer communication emerged as a crucial strategy in the adoption of AAS. Governments, non-governmental organizations, and extension functionaries should make a concerted effort to enhance the continued adoption of AAS by involving local stakeholders in sharing and participating in climate information production, forming farmer’s groups, and focusing on farmers’ literacy toward AAS.